Contemporary Trends in the Standardization of Accounting and Auditing at the International Level - Predrag Šuvakov; Vidosava Sekicki (Journal of Agronomy, Technology and Engineering Management)
This paper explores contemporary trends in the standardization of accounting and auditing practices at the international level, emphasizing the pivotal roles of the International Accounting Standards Board (IASB) and the International Federation of Accountants (IFAC). By harmonizing frameworks such as the International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA), these organizations aim to enhance transparency, comparability, and consistency in financial reporting globally. The study examines key challenges, including the balance between harmonization and localization, the integration of emerging economies, and the cultural and economic barriers to implementation. It also highlights the cost implications for developing nations and small enterprises, advocating for tailored solutions like IFRS for SMEs. Emerging trends such as the integration of Environmental, Social, and Governance (ESG) factors, technological advancements like blockchain and artificial intelligence, and the push for integrated reporting are reshaping the standardization landscape. These developments underscore the need for adaptable and inclusive frameworks to meet evolving stakeholder expectations. We can conclude that while significant strides have been made toward global standardization, ongoing collaboration among regulators, standard-setting bodies, and stakeholders is essential. By addressing challenges and leveraging innovations, the global financial system can achieve greater transparency, reliability, and sustainability, fostering trust and inclusivity in an interconnected economy.